Managemen Continuous Renal Replacement Therapy (CRRT) pada Pasien Gagal Ginjal Akut dan Syok Sepsis di ICU - Fatoni, Arie Zainul; Rusly, Andri; Hartono, Ruddi (Jurnal Klinik dan Riset Kesehatan, 2023)
The incidence of sepsis is around 6% of patients in the hospital. Sepsis that is not manage properly will develop into septic shock which will increase mortality by 50-70%. Acute Renal Failure (ARF) occurs in 58-87% of patients with septic shock. In 70% of cases of ARF caused by sepsis can worsen and require renal replacement therapy (RRT). Continuous Renal Replacement Therapy (CRRT) is a good RRT modality for septic shock patients. A 51 year old male, referred from the ICU another hospital with a diagnosis of respiratory failure, septic shock, Hospital Associated Pneumonia (HAP), diabetic foot with osteomyelitis pedis dextra, ARF Stage 3 and Type 2 Diabetic Mellitus (DM). From the clinical sign, patient was shortness of breath, decreased consciousness, accompanied by shock requiring a vasopressor and from the laboratory obtained urea 277 mg/dl and chest X-ray obtained the impression of pneumonia. The management of this patient was administration of antibiotics, amputation of the right leg and CRRT as a therapeutic modality for ARF. CRRT was performed in Continuous Venovenous Hemodialysis (CVVHDF) mode for 3 days. On the fifth day the patient conditiont improved so he could be discharge from the ICU. At septic shock with ARF, CRRT can maintain hemodynamic stability of patients, remove toxins from the kidneys, remove cytokines and endotoxins, correct acid-base and electrolytes, control fluid volume appropriately, modulate the immune response thereby accelerating renal recovery and improving clinical conditions patient.